Cracking the menopause : while keeping yourself together - Frostrup ,Mariella; Frostrup,Mariella; Smellie, Alice (London, Bluebird, 2022)
It's time for us to start talking about the menopause. Cracking the Menopause, from straight-talking broadcaster Mariella Frostrup and award-winning health journalist Alice Smellie, has all the information you need - with a generous side order of humour. Designed to equip you with the knowledge you need to manage your symptoms from perimenopause onwards, this essential book separates the myths from the reality and offers expertise, hope and advice. Featuring case studies from women in every walk of life and all stages of their menopause journey, Cracking the Menopause opens up the conversation about an urgent topic that half the population will experience, but barely anyone is talking about. Why has the menopause been overlooked in medical research? Why is it ignored by society (except as the butt of bad jokes)? What are the symptoms, when will it happen, and what does it really mean? Answering all these questions and more, Mariella shares her own journey through the menopause - along with the latest science and funny illustrations - to provide an informative source of wisdom, humour and enlightenment. Drawing on cutting-edge research and featuring interviews with a wide range of experts, from leading gynaecologists to psychologists, sleep specialists, nutritionists and more, this book provides advice and recommendations you can trus
Keywords: Health and Fitness